Research on the practice of collaborative teaching mode between python programming course and ideological and political education - Gu Cuihong; Wang Mengxia; Wang Qun (ITM Web of Conferences)
In response to the problem that ideological and political education cannot be well integrated into programming courses, an exploration was conducted on the ideological and political education teaching mode of the "Python Programming" course. Firstly, the current situation of ideological and political education in this course was analyzed. Then, the specific design of the course's ideological and political teaching mode was explored from three aspects: knowledge point introduction, theoretical explanation, and practical application. A collaborative ideological and political teaching mode was constructed that integrates procedural courses with ideological and political education. Finally, the proposed collaborative ideological and political education model was put into teaching practice and its actual effectiveness was evaluated. The practical results have shown that the proposed collaborative ideological and political teaching model has achieved the coordinated integration of curriculum teaching and ideological and political education, stimulated students' subjective initiative in learning, and improved the effectiveness of ideological and political education.